Safety of Accelerated Recovery on a Cardiology Ward and Early Discharge Following Minimalist TAVR in the Catheterization Laboratory: The Vancouver Accelerated Recovery Clinical Pathway. Issue 3 (4th May 2019) - Sathananthan, Janarthanan; Webb, John G; Polderman, Jopie; Achtem, Leslie; Hensey, Mark; Murdoch, Dale; Moss, Robert; Shook, Alyssa; Bruce, Simon; Blanke, Philipp; Bancroft, Carrie; Andrews, Holly; et al.
ABSTRACT: Background: We assessed the safety and efficacy of a clinical pathway with transfemoral transcatheter aortic valve replacement (TAVR) performed in the catheterization laboratory, accelerated recovery on a general cardiology ward and early discharge. Methods: The Vancouver accelerated recovery clinical pathway is an initiative with aims to implement (1) multidisciplinary team selection of patients with lower TAVR procedural risk; (2) peri-procedural minimalist approach with minimal procedural sedation; (3) pre-specified criteria for accelerated transfer to a general cardiology ward; (4) rapid reconditioning post-procedural care; and (5) identification of patients suitable for early (<48 hours) discharge home. Results: A total of 100 prospective patients underwent TAVR with the Vancouver accelerated recovery pathway between September 2016 and August 2018 with a mean age of 79.4 ± 7.4 years and Society of Thoracic Surgeons (STS) score of 3.5 ± 1.7 (55% had STS≥3). Only one (1%) patient needed conversion to general anesthesia, two (2%) patients needed urgent pacemaker implantation for conduction disorder, one (1%) patient had a stroke and five (5%) patients had minor vascular complications. All patients were transferred to the ward but one (1%) patient subsequently needed escalation of care to the coronary care unit. Mean time to first mobilization was 267 ± 60 minutes. Overall, 87 (87%) patients achieved next day discharge and 97 (97%) patients were discharged ≤48 hours. The 30-day mortality was 1% and all-cause readmission rate was 5%. Conclusion: Use of the Vancouver accelerated recovery pathway in highly-selected patients allows TAVR to be performed in the catheterization laboratory followed by accelerated recovery to the ward, with minimal mortality, morbidity, and a high proportion of early discharge. As TAVR continues to expand, this has important implications for health care delivery.